Management of Hospital Waste in Maintaining the Environment - Musri S., M. Ali; Syahlan, Syahlan (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Several areas in Indonesia need more well-developed sanitation infrastructure. Some industries and companies use domestic wastewater disposal systems outside the leading network, a cheaper alternative to centralized systems. The sewage treatment system in these areas typically consists of a septic tank and a medium-scale household wastewater treatment plant. This study aimed to evaluate the effectiveness of SMEC Eye Hospital's liquid waste management after it has been processed through its wastewater treatment system. This experimental research involves managing the liquid waste at SMEC Eye Hospital using an anaerobic-aerobic upflowed biofilter system. The experimental method adheres strictly to a scientific research design. The processed liquid waste is then tested in the laboratory to measure levels of pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), ammonia, oils and fats, and total coliform. The liquid waste from SMEC Eye Hospital was analyzed to determine if the hazardous substances had been reduced or eliminated to meet environmental safety standards. Laboratory tests on the hospital's liquid waste outlet showed that all parameters, including pH, BOD, COD, TSS, ammonia, oil and fat, and total coliform, were within the quality standard limits. To further enhance the environmental safety of the waste, seven steps can be taken to reduce levels of pH, BOD, COD, TSS, ammonia, oil and fat, and total coliform. These measures ensure that the liquid waste from the hospital does not harm the environment.